دور التواصل الرقمي في تحول الأسلوب لدى رسامي البصرة: دراسة في تأثير الفيس بوك - علوان، فريد خالد; يونس، فراس عبدالواحد (جامعة البصرة - مركز دراسات البصرة والخليج العربي, 2016)
تناول مشكلة البحث مفهوم التواصل الرقمي، هذا الرداء المعاصر الذي غلب أنشطتنا اليومية، ومنها الفن التشكيلي، ودور ذلك الوافد المستحدث في إنجاز التحول الأسلوبي عند رسامي محافظة البصرة، الذين يمتلكون صفحات تواصل اجتماعي في كيان الفيس بوك. وجاء البحث في أربعة فصول: اختصا الفصل الأول بالإطار العام للبحث وتحددت فيه مشكلة البحث والحاجة إليه. مع بيان أهمية وجوده. ومن ثم تحديد أهداف البحث المتمثلة في (كشف التحول الأسلوبي لدى رسامي البصرة، بفعل تأثير وسيط التواصل الرقمي عبر أداة الفيس بوك) ثم تقديم الإطار النظري والمؤشرات التي أسفر عنها. وقد حدد الباحث ثلاثة عنوانات ضمنية داخل هذا الإطار تضمنت قراءة موضوعة البحث على وفق أطرها التعريفية المختلفة. وكانت كالآتي: مفهوم الفعل التواصلي/دور الفيس بوك في فعالية التواصل/حراك التشكيل المعاصر في البصرة. أما الفصل الثالث فقد خصص لإجراءات البحث، عبر كشف المجتمع المدروس والعينة المختارة منه ثمانية أعمال) لأربعة من فناني البصرة، قبل استخدام الفيس بوك وأثناء استخدامه. ومن ثم تحديد أداة البحث وتحديد منهجيته، تلا ذلك تحليل العينة. وصولا للفصل الرابع الذي تضمن نتائج البحثو استنتاجاته.
Find addressing the problem of the concept of digital communication, this contemporary garment that has clouded our daily activities, including fine art, and the role of the Creator newcomer in the completion of the stylistic shift when painters province of Basra, who own Social connectedness in Facebook pages entity. The research in four chapters: Chapter One singled out the general framework for research and identified the problem and the need to search. With an indication of the importance of his presence. And then determine the research goals of (revealed stylistic shift to the painters of Basra, under the influence of intermediary digital communication through Facebook tool) and then provide the theoretical framework and indicators that resulted. The researcher identified three Anwanat implied within this framework included the reading placed on the search according to different tariff frameworks. It was as follows: the concept of communicative action / Facebook role in the effectiveness of communication / mobility of contemporary composition in Basra. The third chapter devoted to research procedures, revealed through thoughtful community and the sample selected from eight works) for four of the artists of Basra, before the use of Facebook and during use. And then determine the search tool and determine its methodology, followed by sample analysis. Down for the fourth quarter, which included the results of the research and its findings.
Keywords: التواصل الرقمي -- شبكات التواصل الاجتماعي -- الفيس بوك -- الفنون التشكيلية -- فن الرسم -- البصرة، العراق